Editorial - Alessandro De Gloria (Serious Games Society, 2015)
I am pleased to introduce the first issue of the second year of the IJSG presenting the special issue dedicated to the Games and Learning Alliance Conference (GaLA Conf), that was held in Bucharest in July 2014. The best conference papers were selected and invited for an extended version - with at least one third unpublished content - to be submitted in the regular IJSG evaluation process. In the end of the flow, I am proud to present four papers dealing with learning analytics, user studies for assessing effectiveness of SGs and of their components, and integration of game-based learning in curricula. The issue includes as well one regular paper and a communication for a special issue on mathematics learning games.